Rencana Reklamasi Lahan Bekas Penambangan CV Jati Kencana, di Desa Karangjati, Kecamatan Bergas, Kabupaten Semarang - Wafi, Deta Hibatul; Ratminah, Wawong Dwi (Institut Teknologi Adhi Tama Surabaya, 2019)
Reclamation plans CV Jati Kencana include land management, erosion and sedimentation, and revegetation. Arrangement of the land is done by leveling the layer of cover soil about 85 cm, especially on the base of the quartz and made oblique leads to the water channel with a slope of 1%. Further on the slopes will be made a porch bench equipped with water channels and embankments. Arrangement of land on the basis of quarry is done by using Komatsu D85EX bulldozer with production of one tool of bulldozer 2,184LCM / day, while at level using excavator Caterpillar 320 D with production of one excavator of 643,9LCM / day. The time required to regulate post-mining landform is 87 days. Arrangement of top soil is done with pot system with dimension (0,75x0,75x0,75) m with munjung 0,25 m. The number of planting holes totaling 2,412 holes was done for 19 days. Control of erosion and sedimentation is done by combining mechanical and vegetative methods. Mechanical erosion control is carried out by making terracing bench and drainage making, while vegetative erosion control is done by revegetation of 2,412 plants of marine plants and cover crop of 1,800 vetiver grass. The construction of a trapezoidal waterway with a 60 ° side slope is done for 15 days. Revegetation is done by planting the marine sengon plant with spacing (4x4) m and the covercrop of vetiver grass with plant spacing (0,3x0,3) m.After reclamation there was a decrease in the rate of erosion from 2,298.59ton/ha/yr (Class V, very heavy) at the east and north level to 16.72ton/ha/yr (Class I, very light) and 2,556.55ton/ha/yr (Class V, very heavy) at the west level to 18.07ton/ha/yr (Class I, very light)